Infiltration between the popliteal artery and the capsule of the knee (IPACK) block in knee surgery: a narrative review. Issue 9 (14th May 2021) - Chan, Edmund; Howle, Ryan; Onwochei, Desire; Desai, Neel
Abstract : Background: The infiltration between the popliteal artery and the capsule of the knee (IPACK) block has been described as an alternative analgesic strategy for knee pain. Objective: Our aim was to perform a narrative review to examine the place and value that the IPACK block has in comparison to and in conjunction with other regional anesthesia modalities. Evidence review: Following an extensive search of electronic databases, we included anatomical studies, letters, comparative observational studies, and non-randomized and randomized controlled trials that examined the IPACK block in relation to surgery on the knee under general or neuraxial anesthesia. Findings: In all, 35 articles were included. Cadaveric studies demonstrated the potential for injected dye to spread to the nerves responsible for the innervation of the posterior as well as anteromedial and anterolateral aspects of the knee. Of the comparative observational studies (n=15) and non-randomized (n=1) and randomized controlled trials (n=13), 2 and 27 were conducted in the context of anterior cruciate ligament reconstruction and knee replacement surgery, respectively. The role of the IPACK block with each different permutation of regional anesthesia techniques was investigated by a small number of studies. Clinical studies, in the setting of knee replacement surgery, revealed variation in the manner in which the IPACK block was performed, and indicated the possible superiority of distal injection at the level of the femoral condyles for the management of posterior knee pain. Evidence suggested the following: the IPACK block in combination with single shot adductor canal block (ACB) may be beneficial for analgesic and functional outcomes; in conjunction with single shot or continuous ACB, the IPACK block might be superior to local infiltration analgesia (LIA); and functional outcomes may be improved with the supplementation of continuous ACB and LIA with the IPACK block. The IPACK block did not commonly result in the occurrence of foot drop. Relative to tibial nerve block (TNB), the IPACK block reduced the occurrence of foot drop and increased the proportion of patients who were able to be discharged on the third postoperative day. Conclusions: The IPACK block was potentially complementary to the ACB and might be preferable to the TNB as a motor-sparing regional anesthesia technique in knee surgery. Definitive recommendations were not reached in the presence of the heterogeneous and limited evidence base.